Navigation of Research Methodologies on Health and Academic Performance of Left-Behind Children: A Systematic Review - Sharma, Sushil; Devkota , Bhimsen (Journal of Health Promotion, 2024)
This study focuses on the methodology used to study the health and academic performance of left-behind children (LBC). It examines and analyses the research design, sample, sampling techniques, research tools etc. to assess their uses. The study reflects and represents the context of various countries including Bangladesh, China, Ghana, Nepal during 2010 to 2020. In this methodology 11 studies out of 27 used cross-sectional design. The review followed preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, using JSTOR, Hinari, PubMed and, WorldCat database. These databases provided extensive coverage of relevant literature, and key search terms like ‘parental international migration’, ‘left-behind children’, ‘well-being’, and ‘academic performance’. An initial search of 16,786 articles were narrowed down to 27 studies that met inclusion criteria. Almost all the studies were of quantitative research design effective to capture the relation between parental migration and child well-being and academic performance. The methodology relied on quantitative tools like the self-reported questionnaires, strength and difficulties questionnaires and standardized tests. These tools were important in assessing emotional, behavioral, and academic performance. Anthropometric measurements were widely used to evaluate nutritional status. However, in-depth interview and semi-structured interview were rarely employed despite their value to provide rich and contextual information. Sampling methods varied, with a few studies employing probability proportional sampling for representative data, while others used purposive sampling. The review highlights the need for more longitudinal studies, mixed-method approaches, and broader geographical representation.